Sifat Fisikokimia Produk Bakso Tempe dengan Substitusi Ikan Kembung (Rastrelliger sp.) untuk Strategi Pencegahan Stunting - Novianingrum, Milka Putri; Dewi, Lusiawati (Faculty of Agricultural Technology, Universitas Semarang, 2025)
This study aims to analyze the physicochemical properties of tempe meatball products with the substitution of mackerel (Rastrelliger sp.) as a stunting prevention strategy. Tempe meatballs were substituted with four different levels of mackerel concentration (0 g, 17,2 g, 25,8 g, and 34,4 g) using a one-factor Complete Random Design (RAL) with three replicates. The analysis includes physical (hardness, cohesiveness, gumminess) and chemical (moisture content, ash, fat, protein, carbohydrates, dietary fiber, and free fatty acids). The results showed that the increase in mackerel substitution significantly increased protein content by 23.13% at the best treatment (34.4 g substitution) and improved the physical quality of meatballs. All relevant test parameters have complied with SNI 7266:2017 standards. Thus, mackerel substitution tempe meatballs have the potential to become a highly nutritious functional food to support stunting prevention programs while increasing the added value of local food products.